Tsunami Pendidikan Islam Di Era Digital - Ridwan, Muhamad; Sumiati, Sumiati; Pratiwi, Ananda Audya; Makmur, Makmur (Dahzain Nur, 2025)
This study is motivated by the phenomenon of rapid digitalization and the widespread use of social media among students, which has significantly affected values, morals, and character formation in Islamic education. The main problem addressed in this research is how social media acts as a “tsunami” that shakes the foundations of Islamic education in terms of students’ behavior, ethics, and spirituality. The purpose of this study is to explore teachers’ perspectives on the influence of social media on Islamic education in the digital era. This research employs a qualitative descriptive method with a field research approach. Data were collected through observation, interviews, and documentation involving eight teachers at MTs Al-Ikhlas Poso. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and verification. The findings reveal that social media has both positive and negative impacts; however, teachers perceive its negative effects as more dominant. The observed impacts include declining morality, diminished respect for teachers, social media addiction, reduced learning motivation, and increased impolite behavior and bullying among students. The study concludes that social media has become a “tsunami” in Islamic education due to its massive and destructive influence when not balanced with Islamic values and digital literacy. Therefore, an adaptive Islamic education strategy rooted in akhlakul karimah (noble character) is urgently needed to wisely navigate the wave of digitalization